TINJAUAN HISTORIOGRAFI BUKU PEMERINTAH DARURAT REPUBLIK INDONESIA (PDRI) KARYA MESTIKA ZED - Erasiah Erasiah (Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2018)
The purpose of research to explore the socialcultural and intellectual background of Mestika Zed, to examine the background and objectives of Mestika Zed, analyzes the reconstruction of the PDRI book. The method used in this research is the method of historical research with the heuristic steps of source collection, sourse criticism, interpretation, and writing. The results show that socially and intellectually it is possible Mestika Zed explores information about PDRI because PDRI event occurs in his cultural environment and supported by his intellectual background as a historically-educated historian while writing PDRI is that PDRI’s role is not diverted to interpret its history by anyone, the PDRI is only a point because the textbook for school children agrees or agree Dutch view or history Dutch used to brainwash Indonesian, explaining how mistaken the Dutch looked at Indonesia at that time, explaining the history of PDRI era struggle to open a new field of struggle from city to rural or guerilla. Mestika Zed had a big hand for PDRI’s history that was virtually uncouthed at all. Method used is the historical method that is generally accepted in historical research. The theory or analysis that he used is nationalism with structural and procedural approach.